2005
DOI: 10.1167/iovs.05-0853
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Age-Related Macular Degeneration: Findings from the Andhra Pradesh Eye Disease Study in South India

Abstract: The prevalence of AMD in this south Indian population is similar to those reported in other developed countries. Abstinence from smoking may reduce the risk of AMD in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
119
3
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(141 citation statements)
references
References 68 publications
14
119
3
5
Order By: Relevance
“…247 A south Indian study found a prevalence of AMD in its population similar to other developed countries. 96 A Japanese population study reported similar prevalence of ARM to the white population of the Blue Mountains eye study.…”
Section: Ethnicitymentioning
confidence: 80%
See 2 more Smart Citations
“…247 A south Indian study found a prevalence of AMD in its population similar to other developed countries. 96 A Japanese population study reported similar prevalence of ARM to the white population of the Blue Mountains eye study.…”
Section: Ethnicitymentioning
confidence: 80%
“…95 Cigar smoking in India has also been linked with a higher risk for developing AMD (OR 3.29). 96 A study of Latino subjects also demonstrated an association between smoking and AMD in the Hispanic population (OR 2.4). 97 The effects of passive smoking on AMD risk have been examined in a UK study comparing 435 people with end-stage AMD with 280 healthy controls.…”
Section: -86mentioning
confidence: 94%
See 1 more Smart Citation
“…While AMD has generally been a greater issue in developed countries, studies from India suggest similar prevalence (1.4-1.8%) for late AMD as the population continues to age in developing countries (10,11) . China, on the other hand, has a considerably lower prevalence as confirmed by the Beijing Eye Study (12) .…”
Section: Introductionmentioning
confidence: 99%
“…2 To the best of our knowledge, ANN models have not been established till date for predictions in the areas of ophthalmology. Therefore, the specific purpose of the present report is to train and test the ANN model including developing and validating LR risk score on persons aged 40 to 102 years in a total population (n=3723) and sub-populations drawn using random under sampling technique (n=213) and combination of random under sampling and random over sampling technique (n=1420) for the accurate prediction of AMD.…”
Section: Introductionmentioning
confidence: 99%